Antecedentes del Gobierno Corporativo (GC) - Garzón Castrillon, Manuel Alfonso (2021)
This article aimed to establish the background of corporate governance (CG), the methodology used was content analysis, with a qualitative approach, the type of review is descriptive and the document search strategy was carried out in several stages, the first the investigation of scientific articles, the second the organization of information and the third the writing, an introduction is made, the origins of the CG are discussed, and finally conclusions are reached.